PENGARUH PENAMBAHAN ADJUSTER PADA KOMPOR BRIKET TERHADAP JARAK PEMBAKARAN DAN LAJU PERPINDAHAN PANAS KONDUKSI - Haurissa, Jusuf; Riupassa, Helen; Nanlohy, Hendry; Suyatno, Suyatno (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
The effective and efficient use of biomass briquettes is strongly influenced by the type of stove used and the way it is used. This study aims to design a briquette stove by adding an adjuster: the test fuel used honeycomb briquettes and forest fern charcoal. The heat transfer from burning honeycomb briquettes to a pot of water needs to be maintained so that the heat (temperature) remains constant during the combustion process. In the current use of briquettes, the distance between the briquette flame and the pot of water is unstable because the space is getting further away from the pool of cooking water. The combustion distance is getting farther because the bottom of the initial honeycomb briquettes burns out, causing the surface of the briquettes to decrease and move away from the surface of the water pot. Thus the heat given to the pool of water will reduce. The briquette stove needs to be added with an adjuster to overcome this problem. This adjuster serves to raise the honeycomb briquettes if the surface of the briquettes decreases. With the addition of an adjuster, it will be analyzed how much the heat transfer rate and the stability of the burning distance of the honeycomb briquettes will be. In this study, 2 test models will be used: a stove with an adjuster and a stove without an adjuster, using 14 holes in honeycomb briquettes made from forest ferns using starch (tapioca) adhesive. The distance between the surface of the briquettes and the pot of boiled water is 5 cm. The results showed that the briquette stove using an adjuster could maintain the stability of the combustion distance between the surface of the briquette and the pot of water being cooked with an average temperature t = 567.83 0C and conduction heat transfer q = 5285.699 Watt.